ANALISIS PERAN PENGANGGARAN SEBAGAI ALAT PERENCANAAN DAN PENGENDALIAN MANAJEMEN - Sulistia Ramandani (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Budgeting is far from a mere annual financial routine; it serves as a vital instrument within the management control system to ensure that company operations remain aligned with strategic targets. This study aims to dissect how budgeting fulfills its dual role: as a guiding compass for planning and as a mechanism for organizational control. Utilizing a descriptive qualitative method with a literature review approach, this research evaluates the process from budget formulation to ideal monitoring mechanisms. The analysis reveals that the planning function operates effectively when the budget precisely allocates resources and establishes clear performance targets across all divisions. Concurrently, the control function is realized through variance analysis, which enables management to detect deviations and swiftly implement corrective actions. Nevertheless, challenges such as budgetary slack and rigidity in the face of market shifts remain primary obstacles. This study concludes that successful budgeting demands a balance between realistic planning and flexible, participatory control.